Pengaruh Penerapan Media Pembelajaran Box Jamastik terhadap Hasil Belajar Siswa Kelas III pada Mata Pelajaran Matematika di SDN 106800 Hamparan Perak - Aura Zahra; Astria Ayu Ramadianti; Emy Hariati (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2026)
This study aims to determine the effect of the application of Box Jamastik learning media on the mathematics learning outcomes of third-grade students at SDN 106800 Hamparan Perak. This research was motivated by the low mathematics learning outcomes caused by the use of conventional learning methods that did not actively involve students in the learning process. This study used a quantitative approach with an experimental method and a Non-Equivalent Control Group Design. The sample consisted of 40 students divided into two classes, namely class III-A as the experimental class and class III-B as the control class. Data collection techniques were carried out through pretest and posttest. The data were analyzed using normality tests, homogeneity tests, and paired t-tests. The results showed that the average score of students in the experimental class increased from 54.00 on the pretest to 74.00 on the posttest. Meanwhile, the significance value obtained was 0.000 < 0.05, indicating that the alternative hypothesis was accepted. Therefore, it can be concluded that the application of Box Jamastik learning media has a positive and significant effect on students’ mathematics learning outcomes.